PENTINGNYA KEBERFUNGSIAN KELUARGA DALAM MEMBENTUK KESIAPAN BELAJAR SISWA DI MASA PANDEMI COVID-19 - Rozali, Yuli Asmi; Sitasari, Novendawati Wahyu; M, Safitri (Jurnal Psikologi : Media Ilmiah Psikologi, 2022)
During Covid-19 pandemic, all activities have risks, including activities at school. That’s why we needed learning readiness in implementing health protocols. One of factors affect to learning readiness is the family function. The purpose of this study is to determine affect of family function to student learning readiness during the pandemic. The research methode is quantitative-causal comparative research design, 1 independent variable is family function and dependent variable is learning readiness. The population and subjects in this study are students in Jakarta, 100 students, with random sampling technique and linear regresion analysis statistical. The reliability and validity test obtained (a)= 0.961 ((a) = ≥ 0.7) for the family functioning (a)= 0.883 ((a) = ≥ 0.7) and for the school readiness with each valid item (r)=0.3. The results of statictical test obtained sig. (p) = 0.000; (p) < 0.05, hypothesis accepted, that family functioning affects to student learning readiness during pandemic. And it is also known that family function has 18% to increas students learning readiness. Self awareness and self discipline are predicted to be other factors that affect student learning readiness